-7(6+7p)+7(8p+3)=-35

Simple and best practice solution for -7(6+7p)+7(8p+3)=-35 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(6+7p)+7(8p+3)=-35 equation:


-7(6+7p)+7(8p+3)=-35

We simplify the equation to the form, which is simple to understand
-7(6+7p)+7(8p+3)=-35

Reorder the terms in parentheses
+(-42-49p)+7*(8p+3)=-35

Remove unnecessary parentheses
-42-49p+7+*(+8p+3+)=-35

Reorder the terms in parentheses
-42-49p+(+56p+21)=-35

Remove unnecessary parentheses
-42-49p+56p+21=-35

We move all terms containing p to the left and all other terms to the right.
-49p+56p=-35+42-21

We simplify left and right side of the equation.
+7p=-14

We divide both sides of the equation by 7 to get p.
p=-2

See similar equations:

| -3x-8=-8+3x | | -6(3-6k)+2(8-5k)=-54 | | 3x(4x+9)= | | -120=6(-6-7x) | | -3x^2-22x-7=0 | | -6x^2+5x+21=0 | | -88=-4(-6+7v) | | -4x^2-2x+56=0 | | -3(-4a-5)+6a=105 | | 44=6x-12y | | 44=6x-12 | | 6x-12y=44 | | -2x^2-22x-48=0 | | -3x^2-20x-32=0 | | 2y=6x+10 | | -6x^2-12x+48=0 | | -192=-8(1-3x)+8 | | 3x-1=x+2 | | 4(5x+4)-6= | | 2(3x+2)-3= | | 3(8y-8)-(2y+2)= | | 6(9y-5)-(6y+8)= | | 12a+4b+c=0 | | 81x^8+72x^4+16=0 | | 8x+7y=3 | | -3x^2+4x+11=0 | | 4x^2-3x-11=0 | | 3x^2+4x-11=0 | | 3x^2+11=0 | | 4x-3-7(z+1)=6z | | 24x+6y=54 | | -3x-5(-4x-2)=112 |

Equations solver categories